Forage chemistry and the digestive system in reindeer (Rangifer tarandus tarandus) in northern Norway and on South Georgia
Comparative chemical and botanical analyses of the reticulo-rumen content (RR) and the fill of the digestive system were carried out in free-living Norwegian reindeer Rangifer t. tarandus) on South Georgia (SG) in summer (mean body mass (BM) = 74 kg, n - 10), and in northern Norway in late summer (NS) (mean BM = 77 kg